Hibernal thermal ecology of eastern box turtles within a managed forest landscape1. Issue 2 (23rd August 2012) - Currylow, Andrea F.; Macgowan, Brian J.; Williams, Rod N.
Abstract Box turtles are being extirpated from much of their former range and remaining populations often live in association with anthropogenically altered habitats. This is particularly evident at the northern distributional limit of eastern box turtles (Terrapene carolina carolina) and is an important factor to consider during the winter months when their ability to respond to microclimatic change is limited. Using temperature dataloggers, we studied the hibernal microclimate of box turtles and associated habitat following timber harvests. We monitored the body temperatures of 38 eastern box turtles and collected detailed air and soil profile temperatures of 12 box turtle hibernacula, 6 clearcuts, and 6 adjacent forested areas during the hibernal season (winter 2009–2010). We partitioned the hibernal season into 2 biologically significant thermal periods: hibernation and emergence. The mean hibernation body temperature averaged (3.28° C, SE = 0.09) and corresponded to an average depth of 10 cm. Clearcuts were consistently colder ( <![CDATA[${\bar {x}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37dt619s" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 1.91° C) than forests ( <![CDATA[${\bar {x}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37dt61bb" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 2.68° C) and hibernacula ( <![CDATA[${\bar {x}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37dt61df" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 2.77° C) during hibernation, but became the warmest areas during emergence ( <![CDATA[${\bar {x}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37dt61f0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 9.96° C). We found that in the average clearcut, turtles could burrow to approximately 20 cm to attain the average hibernation body temperature or to approximately 15 cm to attain a body temperature no different than those overwintering on colder, northeast‐facing slopes in the forest ( <![CDATA[${\bar {x}}$]]> <inline-graphic xlink:href="ark:/27927/pgg37dt61gj" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 2.83° C). Alternatively, we found that southwest‐facing slopes were warmer and if turtles chose to overwinter only in clearcuts on those slopes, they could remain shallower. All but 1 turtle overwintered in forested areas; however, our study suggests that some timber harvested areas offer various microhabitats exploitable by hibernating box turtles based on soil profile temperatures, slope aspect, and depth of hibernation. © 2012 The Wildlife Society.